Inactivation of Escherichia coli and Salmonella with Chlorine in Drinking Waters at Various pH and Temperature Levels: Chlorine inactivation of E. coli and Salmonella - Rasheed, Sajida; Hashmi, Imran; Campos, Luiza (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Effect of chlorination at pH 6, 7 and 8 at temperatures 15, 25 and 35˚C for maximum inactivation of Escherichia coli (E. coli) and Salmonella in distilled, tap and well water was examined at 0.25, 0.5 and 1.0 mg/L chlorine. Samples were collected at 0.5, 1, 3, 5, 10, 15, 30 and 45 minutes to determine inactivation through spread plate count (SPC). Among the three types of waters, distilled water was found suitable for better chlorine inactivation as no E. coli counts were detected at 1.0 mg/L of applied chlorine at pH 7 with a 7 log removal with a survival of 0.001 percent. For pH and temperature effect when observed at 0.5 mg/L of applied chlorine dosage showed that the removal was more at pH 7, which was 6 log removal while for temperatures, 35 ºC was found to be optimum with a final E. coli count of 3.0 × 101 CFU/mL with a survival of 0.00025 percent after 45 minutes contact time. Salmonella was found more susceptible to chlorine as compared to E. coli with E. coli count of 8.1×105 and Salmonella count of 3.8×103 CFU/mL after 45 minutes of contact time at 1 mg/L applied chlorine. Salmonella, when tested as monoculture, 7 log removal was observed at 1 mg/L of applied chlorine. So chlorine is found to be an effective disinfectant, provided the optimum temperature of 35ºC and pH 7 for maximum inactivation of E. coli and Salmonella.